Dense SiC containing strongly aligned plate-like grains by magnetic treatment. Issue 3 (April 2015) - Lee, S.H.; Feng, L.; Yin, J.; Lee, J.S.; Zhu, X.; Suzuki, T.S.; Sakka, Y.; Tanaka, H.
Abstract: Dense SiC having strongly aligned plate-like grains was prepared by slip casting under strong magnetic field and subsequent densification using Al3 BC3 additive. Irregular-shaped 6H-SiC powders in the green body were strongly aligned by the magnetic treatment. Subsequently, Al3 BC3 additive induced the formation of aligned plate-like SiC grains during densification. The hardness of SiC could be tailored up to 11% by the strong alignment of the grains. Crack deflection was also strongly affected by the direction of the aligned plate-like grains. As a result, the length of the cracks which propagated parallel to the elongated grains was 18.6% shorter compared to that formed perpendicular to the grains.